Combinatorial Particle Patterning by Nanoxerography. (27th May 2018) - Palleau, Etienne; Ressier, Laurence
Abstract: In their article (https://doi.org/10.1002/adfm.201703511 ), Bojnicic‐Kninski et al. expose the known methods used for creating, on a same substrate, patterns composed of different types of particles. This approach is called "combinatorial particle patterning." They describe various techniques and group them depending on the used methods or driving forces that enable the directed assemblies of particles. A substantial part of the article (Part 2: Electrical Particle Patterning) referred to particle assemblies guided by electrostatic forces, i.e., electrophoretic or dielectrophoretic forces. However, this part, especially the paragraph on "Nanoxerography" (cf. 2.2 of the article) suffers from some inaccuracies that lead to partially wrong conclusions regarding combinatorial particle patterning. The goal of this comment is double: i) giving a complete and up to date definition of nanoxerography ii) reporting the results on combinatorial particle patterning using nanoxerography to correct the article inaccuracies. Abstract : This article is a comment on "Combinatorial Particle Patterning" by Bojnicic‐Kninski et al. (https://doi.org/10.1002/adfm.201703511 ). It gives a complete and up to date definition of the nanoxerography process and reports results on combinatorial particle patterning using nanoxerography to correct some inaccuracies in the published article.